Optimasi Formula Floating Tablet Ranitidin HCLdengan Kombinasi Matriks Hpmc dan Na-CMCMenggunakan Metode Simplex Lattice Design - Agatha, Arinda Garin; , Erindyah R Wikantyasning, Ph.D., Apt (2017)
Ranitidine HCl has a relatively fast half-life of about 2-3 hours so suitable for sustained release tablets made preparations. Drugs used in the study were ranitidine with a combination of matrix is HPMC K4M and Na-CMC for making tablet density lower than gastric acid. The research aims to determine the influence of HPMC K4M and Na-CMC matrix combination on the physical properties, dissolution profile of ranitidin tablet as well as to determine the optimum formula. Tablets were made by wet granulation method with the combination HPMC and Na-CMC for F1 (11,38% : 28,44%), F2 (15,64% : 24,18%), F3 (19,91% : 19,91%), F4 (24,18% : 15,64%), F5 (28,44% : 11,38%). Optimization was designed by Design Expert 10.0.31 (trial) with Simplex Lattice Design method with parameter test was conducted on the flow rate, the angle of repose, tapped density, uniformity of weight, hardness, friability, floating test, floating lag time, and dissolution. The optimum formula that obtained then verified and analyzed with One Sample T-Test with 95% confidence level. The results show that the more HPMC used it will decrease the flow rate, fixed angle, the determination and uniformity of weights fulfill the requirements, hardness and the friability are higher, accelerate the drug in 360 minutes and the release which follow zero order kinetics and Higuchi model. Comparison HPMC 33,45% and Na-CMC 66,55% is the optimum formula proportion